1992
DOI: 10.1099/00207713-42-1-120
|View full text |Cite
|
Sign up to set email alerts
|

Piscirickettsia salmonis gen. nov., sp. nov., the Causative Agent of an Epizootic Disease in Salmonid Fishes

Abstract: A novel intracellular pathogen morphologically similar to the ehrlichiae has been isolated in cell culture and identified as the cause of an epizootic disease of salmonid fish. Like the ehrlichiae, the salmonid pathogen, designated strain LF-89, replicates within membrane-bound cytoplasmic vacuoles in host cells. This agent is the first with characteristics of this type to be isolated from a fish. Analysis of the LF-89 16s rRNA indicated that, unlike the ehrlichiae, LF-89 is a gamma proteobacterium distantly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
220
0
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(227 citation statements)
references
References 18 publications
(2 reference statements)
2
220
0
5
Order By: Relevance
“…At present the molecular phylogenetic placement of Piscin'ckettsia salmonis has been based on the 16s rRNA gene sequence of a single isolate, LF-8gT the type strain (Fryer et al 1992). This analysis showed that P salmonis is a member of the gamma subdivision of the Proteobacteria, as are the genera Coxiella and Francisella.…”
Section: Introductionmentioning
confidence: 99%
“…At present the molecular phylogenetic placement of Piscin'ckettsia salmonis has been based on the 16s rRNA gene sequence of a single isolate, LF-8gT the type strain (Fryer et al 1992). This analysis showed that P salmonis is a member of the gamma subdivision of the Proteobacteria, as are the genera Coxiella and Francisella.…”
Section: Introductionmentioning
confidence: 99%
“…13 The tilapia disease agent (0.57 ϫ 0.8 m) is smaller than the reported size of P. salmonis (0.5 ϫ 1.5 m). 9 The combination of characteristics-different host species, smaller cell size, no response to P. salmonis-specific PCR and P. salmonis-specific fluorescent antibody assays-indicates that the bacterium causing epizootics in tilapia in these cases is not P. salmonis.…”
mentioning
confidence: 99%
“…About half of these were reported in the United States (G. S. Visvesvara, personal communication). Although CNS infections due to Acanthamoeba and Balamuthia have been recorded in animals, such as dogs, sheep, cattle, primates, and horses, 1,4,[9][10][11]15,16 there has been only 1 report of naturally acquired PAM in animals, namely in a South American tapir at a zoo in Arizona. 6 Primary amoebic meningoencephalitis has been experimentally induced in mice, sheep, and monkeys.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 This disease causes high mortality rates and significant economic losses to the salmon industry. 10 Salmonid rickettsial septicemia was first reported in coho salmon, Oncorhynchus kisutch Walbaum, in Chile 2 and has since been observed in other salmonid species, including rainbow trout, Oncorhynchus mykiss Walbaum; Chinook salmon, Oncorhynchus tshawytscha Walbaum; and Atlantic salmon, Salmo salar Linnaeus. 7 Similar rickettsia-like organisms (RLO) have been reported in Atlantic salmon held in salt water in western Canada, 4 Ireland, 17 and Norway.…”
mentioning
confidence: 99%